Know-your-own-League context: insights for player preparation and recruitment - Part 2: Results and goals scored - Buchheit, M.; Hader, K.; Tarascon, A.; McHugh, D.; Verheijen, R. (Sport Performance & Science Reports, 2023)
The aim of this study is to examine the between-league differences in results and goals scored, with reference to match location over a period of 21 league seasons (2001/02 to 2021/22). There weren`t large differences between leagues in terms of average away wins/draws/home wins and the average number of goals scored over the past two decades. The number of goals scored per team tended to be stable over the years within each league and slightly superior for home vs. away teams (1.5 vs. 1 goal, respectively). There were small trends within all leagues for decreased home wins over time (from 50% in 2001/2002 to 40-45% in 2020/2021), while the proportion of draws tended to remain stable - with no large between-leagues differences in these trends.